The Relationship of Anemia in 3rd Trimester Pregnant Women with the Length of the 1st Stage of Latent Phase: Hubungan Anemia pada Ibu Hamil Trimester 3 dengan Lama Kala 1 Fase Laten - Purwanti, Mutiara Frizka Indra; Rosyidah, Rafhani (Indonesian Journal of Innovation Studies, 2021)
Prolonged labor is labor that lasts more than 24 hours in primi and more than 18 hours in multigravida. The incidence of prolonged labor in KB Karunia in 2019-2020 is (79.36%). The purpose of this study was to determine the relationship between anemia and the incidence of prolonged labor in the Karunia family. The population studied were 100 patients and found (79.36%) mothers who had anemia and prolonged labor and (40.54%) mothers who were not anemic experienced normal first stage labor. The research design used in this article is cross-sectional, in which only observations and measurements of variables are carried out at one particular moment. The instruments used are medical records and patient partographs or use secondary data by applying the purposive sampling method. The results showed that the results of the chi square test showed P value of 0.056 > 0.05 which indicated that there was a relationship between the length of the first stage and the incidence of anemia. This shows that anemia in pregnancy has a relationship with the length of the 1st stage. The conclusions mostly show that there is a relationship between anemia and the incidence of the duration of the 1st stage of birth. Family Planning Karunia in 2019-2020.